Well-leg compartment syndrome after robot assisted laparoscopic surgery for rectal cancer: A case report. (March 2023) - Arakawa, Keiichi; Sako, Akihiro
Abstract: Introduction: Lower limb compartment syndrome caused by improper positioning during surgery is called well-leg compartment syndrome. Although well-leg compartment syndrome has been reported in urological and gynecological patients, there have been no reports of well-leg compartment syndrome in patients who have undergone robot-assisted surgery for rectal cancer. Presentation of case: A 51-year-old man was diagnosed with lower limb compartment syndrome by an orthopedic surgeon due to pain in both of his lower legs immediately following robot-assisted surgery for rectal cancer. Due to this, we started placing the patient in the supine position during these surgeries, and repositioned the patient to the lithotomy position following intestinal tract cleansing after rectal movement in the latter half of the surgery. This avoided the long-term effects of being in the lithotomy position. We compared the operation time and complications before and after the above measures were changed, in 40 cases of robot-assisted anterior rectal resection for rectal cancer performed at our hospital from 2019 to 2022. We found no extension of operation time and no occurrence of lower limb compartment syndrome. Discussion: There have been several reports describing the risk reduction of WLCS using intraoperative postural changes. An intraoperative postural change from a natural supine position without pressure which we reported is considered to be a simple preventive method for WLCS. Conclusion: Changing the patient from the supine position to the lithotomy position during surgery may be a clinically acceptable countermeasure to prevent lower limb compartment syndrome. Highlights: A man who was diagnosed with leg compartment syndrome after robotic rectal cancer surgery Changing the patient from the supine position to the lithotomy position during surgery Short term outcome in 40 cases of robot-assisted anterior rectal resection for rectal cancer